66.8k views
3 votes
What are the steps for solving -4+2x=5-(x-3)+3x

User Peter Shaw
by
5.5k points

1 Answer

3 votes

Answer:

I Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.

Explanation:

Simplify

-4 + 2x = 5 + -1(x + -3) + 3x

Reorder your terms

-4 + 2x = 5 + -1(-3 + x) + 3x

-4 + 2x = 5 + (-3 * -1 + x * -1) + 3x

-4 + 2x = 5 + (3 + -1x) + 3x

Combine your like terms 5 + 3 = 8

-4 + 2x = 8 + -1x + 3x

Combineyour like terms -1x + 3x = 2x

-4 + 2x = 8 + 2x

Add -2x to each side of your equation.

-4 + 2x + -2x = 8 + 2x + -2x

Combine your like terms: 2x + -2x = 0

-4 + 0 = 8 + 2x + -2x

-4 = 8 + 2x + -2x

Combine your like terms: 2x + -2x = 0

-4 = 8 + 0

-4 = 8

Solving

-4 = 8

I'm sorry but I Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.

User Spechter
by
5.6k points